2005
DOI: 10.1007/s10147-005-0500-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstruction with free flaps following ablationof oropharyngeal cancer

Abstract: With the development of various reconstructive procedures, most patients who have undergone ablative surgery for oropharyngeal cancer have obtained satisfactory functional results and good quality of life. However, many questions remain concerning methods of obtaining optimal postoperative oral and pharyngeal functions, especially after glossectomy. This review focuses on reconstructive methods after partial glossectomy, hemiglossectomy, and subtotal or total glossectomy and discusses current problems and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…Precise anatomic replacement of the missing tongue seems an intuitive approach but has never been fully described in the literature. A review of literature suggests that previous reports of flap design were largely based on subjective estimation of the defects and contour . Precise measurements of the 3‐dimensional tongue anatomy and flap requirement have not been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise anatomic replacement of the missing tongue seems an intuitive approach but has never been fully described in the literature. A review of literature suggests that previous reports of flap design were largely based on subjective estimation of the defects and contour . Precise measurements of the 3‐dimensional tongue anatomy and flap requirement have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature suggests that previous reports of flap design were largely based on subjective estimation of the defects and contour. 6,7,[12][13][14][15][16][17][18] Precise measurements of the 3-dimensional tongue anatomy and flap requirement have not been described. Such measurements are essential to guide flap design for a 3-dimensinal anatomic reconstruction of hemiglossectomy defects.…”
Section: Discussionmentioning
confidence: 99%
“…Flaps employed for glossectomy defect reconstruction include the medial pterygoid, 15 infrahyoid, 16 sternocleido, 17 pectoralis major, [18][19][20] latissimus dorsi, 21,22 tensor fasciae latae, 23 forearm flap, [24][25][26] rectus abdominal, 7,8,[10][11][12] gracilis, 27 vastus lateralis, 28 lateral thigh flap, [29][30][31] anterolateral thigh flap, 32 and groin flap. 33 Despite these many options, the large defects arising from total/subtotal glossectomy mandate a large flap, which makes the VRAM a common choice.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature revealed a consistent theme in the divergent approaches to achieve the common goal of improved functional reconstruction of the tongue. 12,34 Namely, maintenance of neotongue bulk and convexity yielded improved function. Recently, Yamamoto et al advocated hypoglossal to tenth intercostal nerve VRAM reconstruction to achieve a dynamic semifunctional tongue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation